BRAF-Inhibitor-Induced Metabolic Alterations in A375 Melanoma Cells - Prashant Karki; Shayne Sensenbach; Vahideh Angardi; Mehmet A. Orman (Metabolites, 2021)
Acquired drug tolerance has been a major challenge in cancer therapy. Recent evidence has revealed the existence of slow-cycling persister cells that survive drug treatments and give rise to multi-drug-tolerant mutants in cancer. Cells in this dynamic persister state can escape drug treatment by undergoing various epigenetic changes, which may result in a transient metabolic rewiring. In this study, with the use of untargeted metabolomics and phenotype microarrays, we characterize the metabolic profiles of melanoma persister cells mediated by treatment with vemurafenib, a BRAF inhibitor. Our findings demonstrate that metabolites associated with phospholipid synthesis, pyrimidine, and one-carbon metabolism and branched-chain amino acid metabolism are significantly altered in vemurafenib persister cells when compared to the bulk cancer population. Our data also show that vemurafenib persisters have higher lactic acid consumption rates than control cells, further validating the existence of a unique metabolic reprogramming in these drug-tolerant cells. Determining the metabolic mechanisms underlying persister cell survival and maintenance will facilitate the development of novel treatment strategies that target persisters and enhance cancer therapy.